Analysis Of Factors Influencing Consumer Purchase Intention Of Labuan Bajo Songke Cloth Craft - Yulianus Janur; Dewi Sartika Umul; Akuila Lestin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the factors influencing consumer purchase intention toward songke woven fabric handicraft products at Exotic Komodo Labuan Bajo. The factors examined include product, price, place, and promotion. Data were collected via a quantitative survey using questionnaires distributed to 50 respondents. Multiple linear regression analysis was used to determine the partial and simultaneous effects of each variable on consumers' purchase intention. The results indicate that product, price, place, and promotion variables have a positive and significant influence both partially and simultaneously on the purchase intention of consumers for songke woven fabric handicraft products at Exotic Komodo Labuan Bajo. This study provides recommendations for business actors to optimize these four factors to increase consumer purchase intention.